Intrinsically Fluorescent, Stealth Polypyrazoline Nanoparticles with Large Stokes Shift for In Vivo Imaging. Issue 36 (5th August 2018) - Mane, Shivshankar R.; Hsiao, I‐Lun; Takamiya, Masanari; Le, Dao; Straehle, Uwe; Barner‐Kowollik, Christopher; Weiss, Carsten; Delaittre, Guillaume
Abstract: Recent advances in super‐resolution microscopy and fluorescence bioimaging allow exploring previously inaccessible biological processes. To this end, there is a need for novel fluorescent probes with specific features in size, photophysical properties, colloidal and optical stabilities, as well as biocompatibility and ability to evade the reticuloendothelial system. Herein, novel fluorescent nanoparticles are introduced based on an inherently fluorescent polypyrazoline (PPy) core and a polyethylene glycol (PEG) shell, which address all aforementioned challenges. Synthesis of the PPy‐PEG amphiphilic block copolymer by phototriggered step‐growth polymerization is investigated by NMR spectroscopy, size‐exclusion chromatography, and mass spectrometry. The corresponding nanoparticles are characterized for their luminescent properties and hydrodynamic size in various aqueous environments (e.g., cell culture media). PPy nanoparticles particularly exhibit a large Stokes shift (Δλ = 160 nm or Δν > 7000 cm −1 ) with visible light excitation and strong colloidal stability. While clearance by macrophages and endothelial cells is minimal, PPy displays good biocompatibility. Finally, PPy nanoparticles prove to be long circulating when injected in zebrafish embryos, as observed by in vivo time‐lapse fluorescence microscopy. In summary, PPy nanoparticles are highly promising to be further developed as fluorescent nanodelivery systems with low toxicity and exquisite retention in the blood stream. Abstract : Polypyrazoline‐based nanoparticles are introduced as potent bioimaging agents. Photopolymerization of a tetrazole‐ene AB monomer in the presence of a poly(ethylene glycol)‐ene chain stopper yields a fluorescent amphiphilic polymer, which is excitable with visible light, exhibits a large Stokes shift (7000 cm −1 ), and is able to form biocompatible nanoparticles with long circulation time in the blood stream of a zebrafish model.